2018
DOI: 10.2196/publichealth.7496
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Regionality of the Number of Tweets Related to the 2011 Fukushima Nuclear Power Station Disaster: Content Analysis

Abstract: BackgroundThe Great East Japan Earthquake on March 11, 2011, triggered a huge tsunami, causing the Fukushima Daiichi nuclear disaster. Radioactive substances were carried in all directions, along with the risks of radioactive contamination. Mass media companies, such as television stations and news websites, extensively reported on radiological information related to the disaster. Upon digesting the available radiological information, many citizens turned to social media, such as Twitter and Facebook, to expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Although several previous studies have separately assessed news coverage and social media in pandemic events, only a few of them have compared news coverage with social media (in contrast to other disasters [24][25][26][27][28]). Particularly, Kim et al [29] investigated topic coverage and sentiment dynamics of two different media sources, Twitter and news publications, on the health issue of Ebola virus.…”
Section: Prior Workmentioning
confidence: 99%
“…Although several previous studies have separately assessed news coverage and social media in pandemic events, only a few of them have compared news coverage with social media (in contrast to other disasters [24][25][26][27][28]). Particularly, Kim et al [29] investigated topic coverage and sentiment dynamics of two different media sources, Twitter and news publications, on the health issue of Ebola virus.…”
Section: Prior Workmentioning
confidence: 99%
“…In the future, in order to identify the process by which people’s aversions increase, we want to clarify the feelings that people in a particular region have toward regions that are subject to harmful rumors, such as Fukushima. In a survey by Aoki et al [ 20 ], geotagged tweets made up only 0.25% of the target data; therefore, more comprehensive data are required. In addition, since there are deviations in the age composition and region of Twitter users’ residences, the users are not necessarily representative of the nation as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Since the analysis was also conducted in relation to regions, it did not identify how the interest subsequently formed people’s attitudes toward Fukushima. Aoki et al [ 20 ] surveyed tweeting trends 1 year after the earthquake by dividing regions tweeted about into four zones based on geotags. This analysis only concerned the regions that people were tweeting from and did not analyze the content of the tweets themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Research using social network services (SNS) may help address this particular problem (Babvey et al 2021;Arthur et al 2018;Bennett 2018). Numerous studies have used tweet analysis to evaluate the Great East Japan Earthquake (Aoki et al 2018;Takayasu et al 2015;Jung and Moro 2014). Studies have suggested that negative tweets increase immediately after a disaster and decrease over time (Miura et al 2015), and tweets during a disaster may help reduce psychological stress (Umihara and Nishikitani 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%